Erratum: Pengaruh Status Gizi, Tingkat Aktivitas Fisik dan Kadar Hemoglobin Terhadap Kemampuan Daya Tahan Fisik - Moh Nanang Himawan Kusuma; Muhamad Syafei; Didik Rilastiyo (JUARA : Jurnal Olahraga, 2020)
Correction to: JUARA: Jurnal Olahraga This corrects the article DOI: https://doi.org/10.33222/juara.v4i2.607 This article was originally published using English metadata in the article title and this is our fault. but now the article metadata has been changed in Indonesian and appears correctly in the current article.